Peningkatan Kompetensi Digital Marketing dan Sumber Daya Manusia dalam Rangka Meningkatkan Kapabilitas Desa Wisata Margamulya, Kecamatan Pasirjambu, Kabupaten Bandung - Junipriansa, Donni; Husnul Hanifa, Fanni; Wulandari, Astri (LPPM Politeknik Piksi Ganesha, 2024)
Margamulya Village is a village in Pasirjambu District, Bandung Regency. This village has prominent natural tourism potential, besides that it also has arts potential, such as fire football, reog, karinding, pencak silat and various other attractions. Some of the problems faced by Margamulya Village are limited facilities and infrastructure, limited human resources managing tourist villages, the need for economic empowerment of the surrounding community, both from micro, small, or medium enterprises, and the need to utilize social media as a marketing tool, where a number of these problems need to be solved through training and adaptation of digital marketing, human resources, and increased capabilities. The implementation of the activity took place on June 20, 2024, which was attended by 22 participants who were the target community. The activity received positive appreciation from the community and it is hoped that it can be carried out sustainably.